Validation of the MUSIC Model of Academic Motivation Inventory: Evidence for Use With Veterinary Medicine Students - Jones, Brett D.; Byrnes, Meghan K.; Jones, Mia W. (Frontiers in Veterinary Science, 2019)
The MUSIC Model of Motivation is used to help instructors select strategies that can increase students’ motivation and engagement in courses. The MUSIC model is comprised of five categories of strategies titled: empowerment, usefulness, success, interest, and caring. The purpose of this study was to examine the extent to which the MUSIC Model of Academic Motivation Inventory (College Student version, short-form) demonstrates acceptable psychometric properties when used with students enrolled in a College of Veterinary Medicine. The inventory is comprised of five scales that correspond to the five MUSIC model components and it measures the extent to which a student perceives that: (1) he or she has control of his or her learning environment in the course (empowerment), (2) the coursework is useful to his or her future (usefulness), (3) he or she can succeed at the coursework (success), (4) the instructional methods and the coursework are interesting (interest), and (5) the instructor cares about whether the student succeeds in the coursework and cares about the student’s well-being (caring). The inventory has been validated for use with many different student populations, including students in different countries and of different ages (e.g., college students, middle and high school students, elementary school students). However, the inventory has not been validated for use with veterinary medicine students. We analyzed the data from 578 questionnaires that were obtained from students in six different courses at a College of Veterinary Medicine. To assess the psychometric properties of the inventory, we examined: (a) the internal consistency reliabilities for all of the scales, (b) the fit indices and factor loadings produced from confirmatory factor analyses, and (c) correlations between the MUSIC Inventory scales and students’ self-reported effort in the course. The results provide evidence that the inventory demonstrates acceptable psychometric properties for use with veterinary medicine students. Consequently, instructors and researchers can use the MUSIC Inventory to assess students’ perceptions of the five MUSIC model components.